2005
DOI: 10.1017/s146114570400481x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic antidepressant effects on aggressive, self-injurious and destructive/disruptive behaviours in intellectually disabled adults: a retrospective, open-label, naturalistic trial

Abstract: There is a growing body of evidence that serotonergic antidepressants are useful in the treatment of maladaptive behaviours in the intellectually disabled. However, not all studies have shown positive results due to lack of efficacy, tolerance development, and troublesome side-effects. The current study consisted of a review of the treatment response to a variety of serotonergic antidepressants, consisting of selective serotonin reuptake inhibitors (SSRIs ) (n = 36) and clomipramine (n = 2) in 38 institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…In the same vein, enhancement of serotonergic activity has been reported to decrease aggression in men (Cherek and Lane 2001;Choi-Kwon et al 2006;Coccaro and Kavoussi 1997;Janowsky et al 2005;McCloskey et al 2009) as well as the sex hormone-dependent irritability reported in the luteal phase of the menstrual cycle by women with premenstrual dysphoric disorder (Landén et al 2007;Yonkers et al 2008). Moreover, decreased libido and abolished or delayed orgasm are the most common longterm side effects of these compounds (Montejo-González et al 1997;Waldinger and Olivier 1998); the latter of these effects also having been utilized for therapeutic purposes (Moreland and Makela 2005).…”
Section: Introductionmentioning
confidence: 96%
“…In the same vein, enhancement of serotonergic activity has been reported to decrease aggression in men (Cherek and Lane 2001;Choi-Kwon et al 2006;Coccaro and Kavoussi 1997;Janowsky et al 2005;McCloskey et al 2009) as well as the sex hormone-dependent irritability reported in the luteal phase of the menstrual cycle by women with premenstrual dysphoric disorder (Landén et al 2007;Yonkers et al 2008). Moreover, decreased libido and abolished or delayed orgasm are the most common longterm side effects of these compounds (Montejo-González et al 1997;Waldinger and Olivier 1998); the latter of these effects also having been utilized for therapeutic purposes (Moreland and Makela 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Different modalities of treatment have been tried for selfinjurious behavior. Serotonergic antidepressants are useful in the treatment of self-injurious behaviors in intellectually disabled person (9). Atypical antipsychotics especially risperidone have been used for treatment of aggression and self-injurious behavior (10).…”
Section: Discussionmentioning
confidence: 99%
“…Some patients respond to anticonvulsants such as topiramate or valproic acid (31). Fluoxetine and trazodone have also been used (32). However, the majority of studies on pharmacological treatment of SIB have been performed in adults or in children with autistic spectrum disorders (33).…”
Section: A Behaviour Modificationmentioning
confidence: 99%